A High-Throughput Electrophysiology Assay Identifies Inhibitors of the Inwardly Rectifying Potassium Channel Kir7.1. (July 2015) - Wright, Paul D.; Kanumilli, Srinivasan; Tickle, David; Cartland, Jamie; Bouloc, Nathalie; Dale, Timothy; Tresize, Derek J.; McCloskey, Conor; McCavera, Samantha; Blanks, Andrew M.; Kettleborough, Catherine; Jerman, Jeffrey C.
Kir 7.1 is an inwardly rectifying potassium channel that has been implicated in controlling the resting membrane potential of the myometrium. Abnormal uterine activity in pregnancy plays an important role in postpartum hemorrhage, and novel therapies for this condition may lie in manipulation of membrane potential. This work presents an assay development and screening strategy for identifying novel inhibitors of Kir 7.1. A cell-based automated patch-clamp electrophysiology assay was developed using the IonWorks Quattro (Molecular Devices, Sunnyvale, CA) system, and the iterative optimization is described. In total, 7087 compounds were tested, with a hit rate (>40% inhibition) of 3.09%. During screening, average Z′ values of 0.63 ± 0.09 were observed. After chemistry triage, lead compounds were resynthesized and activity confirmed by IC50 determinations. The most potent compound identified (MRT00200769) gave rise to an IC50 of 1.3 µM at Kir 7.1. Compounds were assessed for selectivity using the inwardly rectifying potassium channel Kir 1.1 (ROMK) and hERG (human Ether-à-go-go Related Gene). Pharmacological characterization of known Kir 7.1 inhibitors was also carried out and analogues of VU590 tested to assess selectivity at Kir 7.1.